Khảo sát đường cong tín hiệu bằng phương pháp Delta và kĩ thuật nhóm điểm - Thành, Lê Tự; Kiếm, Hoàng (Journal of Computer Science and Cybernetics, 2016)
A approach based on the Delta method and the point cluster of the signal curves is suggested. This technic can be effectively applied for studying one wide class of the signal curves at the uncertain conditions.